2017
DOI: 10.1080/00918369.2017.1364558
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Psychometric Properties of the Italian Version of the Homosexuality Scale of the Trueblood Sexual Attitudes Questionnaire

Abstract: The aim of the present study was to translate the Homosexuality scale of the Trueblood Sexual Attitudes Questionnaire into the Italian language and to assess its factor structure and psychometric properties in Italian psychology students. The questionnaire was originally developed and validated in U.S. college students, and later in Turkish social work students, showing high internal consistency. It measures attitudes toward several sexual practices and behaviors, regarding self and others. Particularly, the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Students face significant identity changes as they embark upon university life ( Fino et al, 2018 , 2020 ; Jaspal, 2020 ). These include leaving their families and households, adapting to a new environmental context, creating new relationships and networks, and developing their sexual identities ( Patton et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students face significant identity changes as they embark upon university life ( Fino et al, 2018 , 2020 ; Jaspal, 2020 ). These include leaving their families and households, adapting to a new environmental context, creating new relationships and networks, and developing their sexual identities ( Patton et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low acceptance of one's own sexual behaviour represents a major determinant of psychological distress amongst young adults and student populations (Gegenfurtner and Gebhardt, 2017). In particular, the co-occurence of urban residence, education, and tolerance towards sexual behaviour seems to predict greater tolerance towards and acceptance of a variety of sexual behaviours.…”
mentioning
confidence: 99%
“…Therefore, establishing new sexual health education programs within Turkish nursing education is imperative (Yanıkkerem & Üstgörül, 2020). Although there are a few measuring sexual attitude and studies conducted in different groups, psychometric studies have been found with these and similar scales in samples such as nursing, social worker, and physiotherapy regarding the evaluation of sexual health (Areskoug-Josefsson et al, 2019;Blanc et al, 2018;Fino et al, 2018;Fisher et al, 2013;Gerbild et al, 2017;Shah et al, 2020). However, the nursing education in Turkey part of this scale has been decided that the most appropriate scale for students.…”
Section: Research-article20212021mentioning
confidence: 99%